Accessibility of Pharmaceutical Product Patents for Public Health Through the TRIPs Waiver - Muis, Lidya Shery (Indonesian Journal of Law and Society, 2024)
TRIPs waiver is a bilateral or multilateral agreement proposed by member countries as an exception to the TRIPs agreement during the Covid-19 pandemic. The TRIPs waiver aims to urge WTO member countries to exclude and waive the obligation to protect Intellectual Property Rights and patent flexibility in the form of mandatory licenses, implementation of patents by the government, parallel imports, and bolar provision for the prevention, handling and treatment of Covid-19 during the pandemic. Most of the technology and pharmaceutical products used in handling Covid-19 are objects protected by IPR. This means that anyone is prohibited from producing, selling, importing and exporting these objects without the permission of the IPR holder. So this will hinder the access and availability of pharmaceutical products. This normative juridical study aims to examine the importance of the application of TRIPs waiver in access and availability of pharmaceutical products and examine the policies of WTO member countries towards the proposed implementation of TRIPs waiver. According to the findings of this article, TRIPs waivers are needed in the Covid-19 pandemic, but many regulations must be regulated for their implementation. It is better to use the patent flexibility that has been regulated in each member country. The implementation of patent flexibility can be adjusted according to the abilities of each member country in terms of access and availability of pharmaceutical products during Covid-19. Keywords: Patent, Pharmaceutical Products, Public Health, TRIPs Waiver.